Señoras y señores/Fernando Lamberg - Lamberg, Fernando (Cuba : CASA, 1973)
Obra que nos trae una dramatización delo grotesco.
1. Retratos 2. Esperanza 3. Bodas
Incluye Índice
l. OGen|}
Keywords: LITERATURA CHILENA-POESIA|C